Positive electrode material and battery
By covering carbon material on the core surface of the positive electrode material and controlling the size of graphite crystallites, the problem of low conductivity of the existing positive electrode material is solved, and efficient lithium ion transmission and improved rate performance is achieved.
Patent Information
- Application Number
- CN202510353009.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-25
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2045-03-25
AI Technical Summary
The current cathode materials have low conductivity, limiting their application in lithium-ion batteries.
By covering the carbon material on the core surface of the positive electrode material, the graphite crystallite sizes on the surfaces of the first and second particles are controlled to satisfy 1.3≤La2/La1≤1.91, thereby improving the transmission efficiency and conductivity of lithium ions.
The high ion and electronic conductivity of the positive electrode material is achieved, the deflection efficiency of lithium ions is improved, and the rate performance is improved while ensuring capacity.
Smart Images

Figure CN119905569A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of positive electrode materials, and in particular relates to positive electrode materials and batteries. Background Art
[0002] With the global energy transformation, new clean energy such as wind energy, solar energy, tidal energy, etc. has attracted widespread attention. However, these energy sources are intermittent and uncertain, and an energy storage device is needed to convert them into energy that can be stably stored. As an excellent energy storage device, lithium-ion batteries can convert these new energy sources into electrical energy for long-term storage, and can output these power sources stably when needed. Lithium-ion batteries have been widely used in portable electronic products such as mobile phones, laptops, cameras, etc., and the application of lithium-ion batteries in the field of electric vehicles is also becoming more and more extensive. As a high-performance lithium-ion battery positive electrode material, olivine lithium iron manganese phosphate LiMn x Fe 1-x PO4 (LMFP) and lithium iron phosphate LiFePO4 (LFP), their lower conductivity limits their further application.
[0003] Therefore, how to improve the conductivity of positive electrode materials is one of the problems that needs to be solved urgently. Summary of the invention
[0004] The present application provides a positive electrode material and a battery. The positive electrode material of the present application has both high ionic conductivity and electronic conductivity, which improves the rate performance while ensuring the capacity of the positive electrode material.
[0005] In a first aspect, the present application provides a positive electrode material, the positive electrode material comprising a core and a carbon material located on at least a portion of the surface of the core; the positive electrode material comprises first particles with a particle size of ≤3 μm and second particles with a particle size of ≥8 μm; The positive electrode material is tested by Raman, and the crystallite size of the graphite crystal on the surface of the positive electrode material along the a-axis direction is calculated according to the Tuinstra-Koenig equation as La, , λ is the excitation wavelength of light in Raman testing; The graphite crystallite size on the surface of the first particle is La1 nm, the graphite crystallite size on the surface of the second particle is La2 nm, and the positive electrode material satisfies: 1.3≤La2 / La1≤1.91.
[0006] In some embodiments, the I on the surface of the first particle D / I G The ratio is A, the I D / I G The ratio is B, 1.25≤A / B≤1.7.
[0007] In some embodiments, 2.6 ≤ A ≤ 3.2.
[0008] In some embodiments, 1.8 ≤ B ≤ 2.4.
[0009] In some embodiments, 5.0 ≤ La1 ≤ 6.8.
[0010] In some embodiments, 7.5 ≤ La2 ≤ 10.2.
[0011] In some embodiments, the particle size number distribution curve of the positive electrode material has a peak conforming to the Voigt function distribution, and the particle size distribution width of the particles in the range of 1.5 μm to 11 μm is Span(b), satisfying 1.7 < Span(b) < 2.4.
[0012] In some embodiments, the chemical general formula of the positive electrode material is Li n Mn x Fe y M 1-x-y PO4, where 0.9 ≤ n ≤ 1.2, 0 ≤ x < 0.8, 0.2 < y < 1, and M includes at least one of Ti, Nb, Ta, Ba, Sr, Mg, Zn, V, Mo, Y, and W.
[0013] In some embodiments, the positive electrode material includes secondary particles formed by agglomeration of primary particles, wherein the particle size of the primary particles is 50 nm to 250 nm.
[0014] In some embodiments, the sphericity of the secondary particles is 0.85 to 0.90.
[0015] In some embodiments, the tap density of the positive electrode material is 1.4 g / cm 3 ~1.85 g / cm 3 .
[0016] In some embodiments, the specific surface area of the positive electrode material is 7 m 2 / g~15 m 2 / g.
[0017] In some embodiments, the compression density of the positive electrode material is 2.05 g / cm 3 ~2.35 g / cm 3 .
[0018] In some embodiments, the pH value of the positive electrode material is 9.5 to 10.5.
[0019] In some embodiments, the oil absorption value of the positive electrode material is 20 mL / 100g to 40 mL / 100g.
[0020] In some embodiments, the powder resistivity of the positive electrode material is 10-100 Ω·m.
[0021] In some embodiments, the mass content of carbon element in the positive electrode material is 1.4wt%~1.7wt%.
[0022] In some embodiments, the mass content of the magnetic substance in the positive electrode material is 0.1-0.75 mg / kg.
[0023] In a second aspect, the present application provides a battery, comprising a positive electrode material.
[0024] Compared with the prior art, the present invention has the following beneficial effects: The positive electrode material provided by the present application has a core surface of the positive electrode material coated with a carbon material in at least a part of its area, and the graphite crystallite size La1 in the carbon material on the surface of the first particle with a small particle size and the graphite crystallite size La2 in the carbon material on the surface of the second particle with a large particle size. Since the electron transmission path of the second particle with a large particle size is long and the electron transmission path of the first particle with a small particle size is short, the inventors found in the course of research that by controlling the graphite crystallite size on the surface of the first particle and the second particle to satisfy: 1.3≤La2 / La1≤1.91, the surface of the second particle with a large particle size forms a graphite crystallite size with a larger size along the a-axis direction, and the large-sized graphite crystallite along the a-axis direction can transmit electrons faster, and due to ion-coupled electron transfer, the transmission efficiency of lithium ions on the surface of the second particle can also be greatly improved, which is conducive to improving the efficiency of lithium ion deintercalation. The surface of the first particle with a small particle size forms graphite crystallites with a smaller size along the a-axis direction. Since the first particle itself has a smaller particle size, the first particle can have a higher ion and electron transmission efficiency, and the graphite crystallites with a smaller size have less influence on the electron and ion transmission of the first particle, so that the first particle and the second particle in the positive electrode material can present a high degree of lithium ion conduction consistency as a whole; in addition, the surface of the first particle forms a smaller graphite crystallite size, which can inhibit the growth of primary particles in the first particle and reduce the capacity attenuation caused by excessive growth of primary particles in the first particle. Therefore, the positive electrode material of the present application has good conductivity, capacity and rate performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] In order to more clearly illustrate the embodiments of the present application or the technical solutions of the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0026] Figure 1A schematic diagram of the discharge state of a battery provided in an embodiment of the present application.
[0027] Figure 2 This is a SEM image of the positive electrode material prepared in Example 1 of the present application; Figure 3 The Raman spectrum of the positive electrode material prepared in Example 1 of the present application; Figure 4 A schematic diagram of 30 test points selected for the Raman test of the positive electrode material prepared in Example 1 of the present application; Figure 5 This is the EDS spectrum of carbon elements on the surface of the positive electrode material prepared in Comparative Example 1 of the present application. DETAILED DESCRIPTION
[0028] In order to better understand the technical solution of the present application, the embodiments of the present application are described in detail below with reference to the accompanying drawings.
[0029] It should be clear that the described embodiments are only part of the embodiments of the present application, rather than all the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present application.
[0030] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Thus, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features.
[0031] In order to easily understand the present invention, specific terms are appropriately defined in this application. Unless otherwise defined herein, scientific terms and technical terms used in the present invention have the meanings commonly understood by those skilled in the art to which the present invention belongs.
[0032] The present application provides a positive electrode material, the positive electrode material comprising a core and a carbon material located on at least a portion of the surface of the core; the positive electrode material comprises first particles with a particle size of ≤3 μm and second particles with a particle size of ≥8 μm; The positive electrode material is tested by Raman, and the crystallite size of the graphite crystal on the surface of the positive electrode material along the a-axis direction is calculated according to the Tuinstra-Koenig equation as La, , λ is the excitation wavelength of light in Raman testing; The graphite crystallite size on the surface of the first particle is La1 nm, the graphite crystallite size on the surface of the second particle is La2 nm, and the positive electrode material satisfies: 1.3≤La2 / La1≤1.91.
[0033] The positive electrode material provided by the present application has a core surface of the positive electrode material coated with a carbon material in at least a part of its area, and the graphite crystallite size La1 along the a-axis direction in the carbon material on the surface of the first particle with a small particle size and the graphite crystallite size La2 along the a-axis direction in the carbon material on the surface of the second particle with a large particle size. Since the electron transmission path of the second particle with a large particle size is long and the electron transmission path of the first particle with a small particle size is short, the inventors found in the course of research that by controlling the graphite crystallite size on the surface of the first particle and the second particle to satisfy: 1.3≤La2 / La1≤1.91, the surface of the second particle with a large particle size forms a graphite crystallite with a larger size along the a-axis direction, and the large-sized graphite crystallite along the a-axis direction can transmit electrons faster, and due to ion-coupled electron transfer, the transmission efficiency of lithium ions on the surface of the second particle can also be greatly improved, which is conducive to improving the insertion and extraction efficiency of lithium ions. The surface of the first particle with a small particle size forms graphite crystallites with a smaller size along the a-axis direction. Since the first particle itself has a smaller particle size, the first particle can have a higher ion and electron transmission efficiency, and the graphite crystallites with a smaller size along the a-axis direction have less effect on the electron and ion transmission of the first particle, so that the first particle and the second particle in the positive electrode material can present a high degree of lithium ion conduction consistency as a whole; in addition, the surface of the first particle forms a smaller graphite crystallite size, which can inhibit the growth of primary particles in the first particle and reduce the capacity attenuation caused by excessive growth of primary particles in the first particle. Therefore, the positive electrode material of the present application has good conductivity, capacity and rate performance.
[0034] In some embodiments, the I D / I G The value is A, the I of the surface of the second particle with a particle size of ≥8μm D / I G Value is B, I D / I G The value of can characterize the degree of graphitization of the carbon material. In the present application, 1.25≤A / B≤1.7 is controlled so that the degree of graphitization on the surface of the first particle and the degree of graphitization on the surface of the second particle can be controlled within an appropriate range, so that the surface of the second particle with a large particle size has a carbon material with a higher degree of graphitization, and electrons can quickly transfer electrons in the carbon material with a higher degree of graphitization, which can improve the electronic conductivity and ion transmission efficiency of the second particle with a large particle size; at the same time, the surface of the first particle with a small particle size has a carbon material with a relatively low degree of graphitization, and the small graphite crystallites are not sufficient to affect the excellent electron and ion transmission performance of the first particle, so that the positive electrode material as a whole presents a high degree of lithium ion conduction consistency.
[0035] Specifically, A / B can be 1.25, 1.26, 1.28, 1.3, 1.35, 1.4, 1.45, 1.5, 1.56, 1.62, 1.69, 1.7 or any value therebetween, which is not limited here. When the ratio of A / B is too large, the surface of the first particle with a small particle size is generally D / I G The value increases, that is, the proportion of amorphous carbon (sp3 carbon) is greater, which is easy to form a poor conductive area, the electronic conductivity of the small-sized first particles decreases, and the size of the graphite crystallites along the a-axis direction decreases, and the electronic conductivity of the positive electrode material decreases. When the A / B ratio is too small, it is generally the surface I of the small-sized first particles. D / I G The value decreases, that is, the carbon material on the surface of the first particle decreases, and the primary particles in the first particle are prone to overgrowth and become single crystal particles with large particle size (that is, overburning phenomenon). The large single crystal particles have low lithium ion transmission efficiency, resulting in a decrease in the capacity of the positive electrode material.
[0036] In this application, the positive electrode material is tested by Raman. There are characteristic peaks of D and There are G characteristic peaks at , which correspond to the sp3 defective carbon and sp2 ordered carbon of C, respectively. By fitting the peak shape of Raman data, the areas of these two peaks can be obtained, i.e., I D / I G The value is the peak area ratio of the D characteristic peak and the G characteristic peak.
[0037] In some embodiments, the I on the surface of the first particle D / I G The ratio is A, 2.6≤A≤3.2, and the A value can specifically be 2.6, 2.7, 2.8, 2.9, 3.0, 3.1, 3.2 or any value therebetween, which is not limited here.
[0038] In some embodiments, the second particle surface I D / I G The ratio is B, 1.8≤B≤2.4, and the B value can specifically be 1.8, 1.9, 2.0, 2.1, 2.2, 2.3, 2.4 or any value therebetween, which is not limited here.
[0039] In some embodiments, the size of the graphite crystallites on the surface of the first particle along the a-axis is La1 nm, the size of the graphite crystallites on the surface of the second particle along the a-axis is La2 nm, 1.3≤La2 / La1≤1.91, La2 / La1 can specifically be 1.3, 1.35, 1.4, 1.45, 1.5, 1.55, 1.6, 1.65, 1.7, 1.75, 1.8, 1.85, 1.91 or any value therebetween, which is not limited here. When La2 / La1 is too large, the difference between the graphite crystallite size on the surface of the second particle with large particle size and the graphite crystallite size on the surface of the second particle with small particle size is too large, the graphite crystallite size on the surface of the second particle with large particle size is too large, and the carbon coating layer on the surface of the second particle is too thick, which inhibits the lithium ion deintercalation performance on the surface of the second particle. At the same time, the small graphite crystallite on the surface of the first particle is not enough to affect the excellent electron and ion transmission performance of the first particle, resulting in an increase in the difference in lithium ion deintercalation performance between particles of different particle sizes in the positive electrode material, and the overall lithium ion conduction consistency of the positive electrode material is low. When La2 / La1 is too small, the difference between the graphite crystallite size on the surface of the second particle with large particle size and the graphite crystallite size on the surface of the first particle with small particle size is small, and it is difficult to significantly improve the lithium ion deintercalation performance on the surface of the second particle and slightly increase the lithium ion deintercalation performance on the surface of the first particle at the same time, resulting in an increase in the difference in lithium ion deintercalation performance between particles of different particle sizes in the positive electrode material, and the overall lithium ion conduction consistency of the positive electrode material is low.
[0040] In some embodiments, the graphite crystallite size on the surface of the first particle is La1 nm, 5.0≤La1≤6.8, and the La1 value can specifically be 5.0 nm, 5.1 nm, 5.2 nm, 5.3 nm, 5.5 nm, 5.8 nm, 6.0 nm, 6.2 nm, 6.4 nm, 6.8 nm or any value therebetween, which is not limited here.
[0041] In some embodiments, the graphite crystallite size on the surface of the second particle is La2 nm, 7.5≤La2≤10.2, and the graphite crystallite size can specifically be 7.5nm, 7.8nm, 8.0nm, 8.5 nm, 9.0 nm, 9.5 nm, 9.8 nm, 10.0nm, 10.2 nm or any value therebetween, which is not limited here.
[0042] In some embodiments, the chemical formula of the positive electrode material is Li n Mn x Fe y M 1-x-yPO4, where 0.9 ≤ n ≤ 1.2, 0 ≤ x < 0.8, 0.2 < y < 1, and M includes at least one of Ti, Nb, Ta, Ba, Sr, Mg, Zn, V, Mo, Y, and W.
[0043] Specifically, the value of n can be specifically 0.90, 0.92, 0.95, 0.96, 0.98, 0.99, 1.0, 1.05, 1.08, 1.1, or 1.2, etc.; the value of x can be specifically 0, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, or 0.79, etc.; the range of the value of y can be 0.21, 0.28, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.85, 0.9, 0.95, or 0.99, etc. Of course, it can also be other values within the above range, which are not limited herein.
[0044] It should be noted that the content of each element in the cathode material can be determined by well-known instruments for qualitative analysis and / or quantitative analysis of each element, such as ICP and ICP-MS.
[0045] In some embodiments, the cathode material includes secondary particles formed by agglomeration of primary particles. Specifically, the secondary particles are spherical in structure, and the primary particles in the secondary particles are tightly combined to form secondary particles, which is beneficial to improving the tap density of the cathode material.
[0046] In some embodiments, the secondary particles are spherical particles. It can be understood that the surface curvature of the spherical secondary particles tends to be consistent, and the uniformity of the carbon material coating on its surface is improved, which can increase the conductivity of the particles.
[0047] In some embodiments, the sphericity of the secondary particles is 0.85 - 0.90. For irregular cathode material particles, local accumulation of carbon materials is likely to occur, resulting in poor conductivity in some areas, and the electron conduction between particles is easily affected. By controlling the sphericity of the secondary particles in the present application within the above range, the uniformity of the carbon material coating on the particle surface can be improved, and at the same time, the graphitization degree of the surfaces of particles with different particle sizes can be controlled. Under the synergistic effect of the particle sphericity and graphitization degree, the electronic conductivity of the cathode material can be further improved.
[0048] In some embodiments, the particle size of the primary particles is 50nm - 250nm, specifically it can be 50nm, 80nm, 100nm, 120nm, 140nm, 160nm, 200nm, 210nm, 230nm, 250nm, or any value between them, which is not limited herein.
[0049] In some embodiments, at least part of the surface of the core has a carbon material, and the carbon material forms a coating layer, and the thickness of the carbon layer is measured by transmission electron microscopy to be about 2nm to 5nm. The formation of a carbon layer on the surface of the positive electrode material particles is beneficial to improving electronic conductivity.
[0050] In some embodiments, the carbon material includes amorphous carbon and graphitized carbon. That is, the carbon material is a metastable amorphous carbon material having sp1, sp2 and sp3 hybridization at the same time. Among them, sp2 ordered carbon has a π bond, and electrons can move freely in the conjugated system. Sp2 ordered carbon has better conductivity than sp3 defective carbon.
[0051] In some embodiments, the core may be lithium iron phosphate or lithium iron manganese phosphate. Preferably, the core may be lithium iron manganese phosphate.
[0052] In some embodiments, the particle size distribution curve of the positive electrode material has a peak that conforms to the Voigt function distribution, and the particle size distribution width of particles in the range of 1.5 μm to 11 μm is , satisfying 1.7< <2.4.
[0053] Specifically, it can be 1.71, 1.72, 1.80, 1.83, 1.9, 1.95, 2.0, 2.15, 2.2, 2.34 or 2.39, etc., which are not limited here. Preferably, Satisfy 1.9< <2.1.
[0054] The peaks in the particle size range of 1.5μm~11μm in the number distribution spectrum conform to the Voigt function distribution. At the same time, the sharper the peak, the narrower the half-peak width, indicating that the positive electrode material particles have good dispersion. Particles of different sizes fill each other, which can increase the compaction density of the positive electrode material and improve the energy density of the positive electrode material.
[0055] In some embodiments, the specific surface area of the positive electrode material is 7m² / g to 15m² / g; specifically, it can be 7m² / g. 2 / g, 8m 2 / g, 9m 2 / g, 10m 2 / g, 11 m 2 / g, 12m 2 / g, 13m 2 / g, 14 m 2 / g, 15 m 2 / g or any value therebetween, which is not limited herein. By controlling the specific surface area of the positive electrode material within the above range, the positive electrode material can exhibit higher capacity, first coulombic efficiency, cycle stability and lower gas generation.
[0056] In some embodiments, the tap density of the positive electrode material is 1.4 g / cm 3 ~1.85 g / cm 3 , specifically 1.4 g / cm 3 , 1.45 g / cm 3 , 1.5 g / cm 3 , 1.55g / cm 3 , 1.6 g / cm 3 , 1.65 g / cm 3 , 1.7g / cm 3 , 1.75g / cm 3 , 1.80g / cm 3 , 1.85g / cm 3 Controlling the tap density of the positive electrode material within the above range is beneficial to improving the processing performance of the material and increasing the energy density of the battery.
[0057] In some embodiments, the compaction density of the positive electrode material is 2.05 g / cm 3 ~2.35g / cm 3 , specifically 2.05 g / cm 3 , 2.06 g / cm 3 , 2.09g / cm 3 , 2.1 g / cm 3 , 2.12 g / cm 3 , 2.15g / cm 3 , 2.18g / cm 3 , 2.2g / cm 3 , 2.22g / cm 3 , 2.25g / cm 3 , 2.35g / cm 3 Controlling the compaction density of the positive electrode material within the above range is beneficial to improving the energy density of the battery.
[0058] In some embodiments, the pH value of the positive electrode material is 9.5-10.5, specifically 9.5, 9.7, 9.8, 9.9, 10.0, 10.1, 10.2, 10.4, 10.5 or any value therebetween, which is not limited here. Controlling the pH of the positive electrode material within the above range is conducive to improving the processing performance of the positive electrode material.
[0059] In some embodiments, the oil absorption value of the positive electrode material is 20 mL / 100g to 40 mL / 100g, specifically 20 mL / 100g, 22 mL / 100g, 25 mL / 100g, 28 mL / 100g, 29 mL / 100g, 30 mL / 100g, 32 mL / 100g, 34 mL / 100g, 35 mL / 100g, 38 mL / 100g, 40 mL / 100g or any value therebetween, which is not limited here. The oil absorption value of the positive electrode material is related to the pore ratio of the positive electrode material. In the process of preparing the positive electrode slurry, if the oil absorption value of the positive electrode material is too high, the amount of dispersant and binder required for preparing the slurry will increase, that is, the mass ratio of the positive electrode material in the positive electrode slurry will decrease, the battery energy density will be reduced, and the processing cost will be increased; when the oil absorption value of the positive electrode material is too low, the dispersibility of the positive electrode material in the positive electrode slurry will decrease. In the present application, without affecting the processing performance and processing cost of the positive electrode material, the oil absorption value of the positive electrode material is controlled within the above range, which is beneficial to improving the compatibility of the positive electrode material with the electrolyte. The positive electrode material has better adsorption and wetting properties for the electrolyte, which can effectively reduce the interface resistance between the positive electrode material and the electrolyte, which is beneficial to improving the transmission of lithium ions and electrons, and making the electrochemical performance of the positive electrode material better.
[0060] In some embodiments, the powder resistivity of the positive electrode material is 10Ω·m~100Ω·m, specifically 10Ω·m, 20Ω·m, 30Ω·m, 40Ω·m, 50Ω·m, 80Ω·m, 100Ω·m or any value therebetween, which is not limited here.
[0061] In some embodiments, the mass content of carbon in the positive electrode material is 1.4wt%~1.7wt%; specifically, it can be 1.4 wt%, 1.45 wt%, 1.5 wt%, 1.55 wt%, 1.6 wt%, 1.65wt%, 1.7 wt% or any value therebetween, which is not limited here. If the carbon content of the positive electrode material is too high, the capacity of the positive electrode material will decrease; if the carbon content of the positive electrode material is too low, the integrity of the carbon layer coating on the surface of the positive electrode material will decrease, the side reaction between the positive electrode material and the electrolyte will intensify, and the electronic conductivity of the positive electrode material will be greatly reduced. The present application controls the mass content of carbon in the positive electrode material within the above range, which is conducive to obtaining a positive electrode material with high capacity and high electronic conductivity.
[0062] In some embodiments, the mass content of the magnetic substance in the positive electrode material is 0.1 mg / kg ~ 0.75 mg / kg, specifically 0.1 mg / kg, 0.2 mg / kg, 0.3 mg / kg, 0.4 mg / kg, 0.5 mg / kg, 0.6 mg / kg, 0.7 mg / kg, 0.75 mg / kg or any value therebetween, which is not limited here. Magnetic substances have the risk of causing short circuits. If there are too many magnetic foreign bodies in the positive electrode material of the battery, such as iron, chromium, nickel, etc., these foreign bodies may move inside the battery and pierce the diaphragm, causing the battery to short circuit. The present application controls the magnetic substance within the above range, which is conducive to improving the safety of batteries prepared from positive electrode materials.
[0063] In a second aspect, the present application provides a method for preparing a positive electrode material, comprising the following steps: S10, premixing a mixed solution containing a carbon source, a dispersant and water, and then adding a lithium source, a phosphorus source, an iron source and a dopant, stirring evenly to obtain a feed solution; S20, grinding the liquid material and adding an embedding agent to obtain a slurry, and spray drying the slurry to obtain a precursor; S30, sintering the precursor to obtain a positive electrode material, wherein the sintering process includes a first stage, a second stage and a third stage performed in sequence, wherein the sintering temperature of the first stage is 200°C~600°C, the sintering temperature of the second stage is 650°C~700°C, and the sintering temperature of the third stage is 750°C~800°C.
[0064] The preparation method of the positive electrode material provided in the present application is to mix the components by wet method to form a liquid, and add a dispersant to fully disperse the carbon source. After grinding, an embedding agent is added. The embedding agent can be evenly distributed on the surface of the spray material during the spraying process, which is conducive to subsequent carbonization. A secondary particle precursor with high sphericity is obtained by spray drying, and finally sintering treatment is performed. During the sintering process, the carbon source on the surface of the secondary particles is first melted. When the temperature rises to above 200°C, the carbon source is dehydrated to form a coke-like compound. After the sintering temperature is further increased, further dehydrogenation and deoxidation are performed to produce disordered hexagonal carbon planes, that is, graphite microcrystals are generated, and most of the carbon source is converted into sp3 carbon (amorphous carbon) with a disordered structure. The sintering temperature continues to rise, and some graphite microcrystal sheets that are roughly in the same plane gradually combine into a new plane body, that is, short-range ordered sp2 carbon (graphitized carbon). The preparation method of the present application is that the embedding agent and the carbon source can cooperate with each other so that the carbon material on the surface of the positive electrode material obtained by sintering can have an appropriate degree of graphitization. The sintering treatment is conducive to the conversion of more sp3 carbon to sp2 carbon. At the same time, the segmented high-temperature sintering is used to prevent the matrix material from excessive growth and causing overburning. In addition, due to the difference in the size of the secondary particles, carbon layers with different sp3 carbon / sp2 carbon ratios are formed on the surfaces of the secondary particles of different particle sizes. Particles of different particle sizes are adapted to an appropriate degree of graphitization, so that the first particles and the second particles in the positive electrode material satisfy 1.3≤La2 / La1≤1.91, 1.25≤A / B≤1.7, so that the electronic conductivity of different particles tends to be close, so that the positive electrode material has both high ionic conductivity and electronic conductivity, while ensuring the capacity of the positive electrode material, the rate performance is improved.
[0065] The preparation method of the present application is described in detail below with reference to the examples: S10, premixing a mixed solution containing a carbon source, a dispersant and water, and then adding a lithium source, a phosphorus source, an iron source and a dopant, stirring evenly to obtain a feed solution.
[0066] In some embodiments, the carbon source includes at least one of a monosaccharide, a polysaccharide, and a soluble sugar source.
[0067] In some embodiments, the carbon source includes at least two of polyvinyl alcohol monohydrate, ascorbic acid, galactose, maltose, arabinose, fructose, glucose and sucrose. The applicant has found through testing that when a monosaccharide or a soluble sugar source is used alone, wall adhesion may occur during the spray drying process, affecting the morphology of the particles and the distribution of carbon materials on the surface of the particles. Preferably, the carbon source is a mixture of glucose monohydrate and maltose.
[0068] In some embodiments, the mass content of the carbon source in the slurry is 2% to 4%, specifically 2%, 2.3%, 2.5%, 3%, 3.5%, 3.8%, 4% or any value therebetween, which is not limited here. Too much addition of carbon source will affect the degree of graphitization of the carbon coating layer on the surface of the positive electrode material during the sintering process. It is difficult to drive most of the sp3 carbon material to convert to sp2 carbon material under the same heat, resulting in an increase in the proportion of sp3 carbon material in the final prepared positive electrode material, affecting the conductivity and compaction properties of the positive electrode material. If the amount of carbon source added is too low, there is not enough carbon source to effectively coat the lithium manganese iron phosphate. During the sintering process, part of the lithium manganese iron phosphate material undergoes redox reaction, affecting the capacity of the positive electrode material.
[0069] In some embodiments, the dispersant includes at least one of an anionic wetting dispersant and a polymeric super dispersant. For example, the anionic wetting dispersant may be sulfonic acid succinates, dodecyl sulfonates, citric acid, etc., and the polymeric super dispersant may be polyvinyl pyrrolidone PVP, polyethylene glycol PEG, etc. In the technical solution of the present application, since an appropriate amount of dispersant is added to the slurry, the presence of the dispersant can enable each component in the slurry to utilize a steric hindrance effect or an electrostatic stabilization mechanism so that each component in the slurry can remain relatively stable.
[0070] In some embodiments, the dispersant includes dodecyl sulfonate, which is adsorbed on the surface of solid particles (such as lithium source, manganese source, etc.), reduces the surface tension between solid and liquid, and makes the surface of condensed solid particles easy to wet. The dispersant acts on the particle clusters through electrostatic forces, van der Waals forces or hydrogen bonds, etc., so that the solid particles can be fully dispersed and the re-aggregation of solid particles can be effectively reduced. Dodecyl sulfonate forms a bilayer structure on the surface of solid particles, and the polar end of the outer dispersant has a strong affinity with water, which increases the degree of wetting of solid particles by water. In the subsequent spray drying process, the carbon source particles are not prone to local agglomeration, and the carbon source particles are evenly distributed around the solid particles, which improves the uniformity of carbon source distribution and is conducive to improving the conductivity of the positive electrode material.
[0071] In some embodiments, the molecular weight of the polymeric hyperdispersant is 800-2500, which is not limited herein.
[0072] In some embodiments, the lithium salt may be selected from lithium carbonate, lithium hydroxide, etc. The phosphorus source may be selected from phosphoric acid, iron phosphate, manganese phosphate, ferromanganese phosphate, etc. The iron source may be selected from ferrous oxalate, iron phosphate, ferromanganese phosphate, iron powder, etc.
[0073] In some embodiments, an appropriate amount of manganese source is also added to the feed solution, and the manganese source can be selected from manganese tetraoxide, manganese dioxide, and ferromanganese phosphate.
[0074] In some embodiments, the amount of the lithium salt added is 1.02 to 1.05 times the theoretical amount to ensure that sufficient lithium ions can be inserted and removed.
[0075] In some specific implementations, S10 specifically includes: Adding an organic carbon source and a dispersant to a portion of pure water, stirring and mixing once, to obtain a first mixture; The remaining pure water and the lithium-containing phosphate or its raw salt are added to the first mixture, and the mixture is stirred and mixed for a second time to obtain a feed liquid.
[0076] In some embodiments, the conductivity of pure water is ≤ 0.165 μs / cm.
[0077] In some embodiments, the first stirring time is 10 min to 20 min, and the second stirring time is 1 h to 2 h.
[0078] S20, grinding the liquid material and adding an embedding agent to obtain a slurry, and spray-drying the slurry to obtain a precursor.
[0079] In some embodiments, grinding includes coarse grinding and fine grinding.
[0080] In some embodiments, the average particle size of the particles in the slurry after coarse grinding is ≤1.2 μm.
[0081] In some embodiments, the average particle size of the particles in the finely ground liquid is 0.2 μm to 0.4 μm.
[0082] It can be understood that through coarse grinding and fine grinding, the particle size in the slurry can be controlled within an appropriate range, which is beneficial to improve the capacity of the positive electrode material and the lithium ion transmission efficiency. When the average particle size of the particles in the ground liquid is too small, these small particles are prone to overburning during the sintering process, affecting the capacity of the positive electrode material. When the average particle size of the particles in the ground liquid is too large, the transmission path of the lithium ions of the positive electrode material increases and the lithium ion transmission efficiency decreases. The present application controls the particle size in the slurry within the above range, which can increase the tap density of the particles, increase the compaction density of the positive electrode material, and ensure the capacity and conductivity of the positive electrode material.
[0083] In some embodiments, the embedding agent includes at least one of maltodextrin and polystyrene resin. Preferably, the embedding agent is maltodextrin MD10. That is, maltodextrin with a DE value of 10, wherein the DE value is the number of dehydrated α-D glucose units, i.e., the reducing end. The properties of maltodextrin are directly related to the DE value. When the DE value of maltodextrin is 4 to 6, its sugar composition is all larger molecules above tetrasaccharides. When the DE value is 9 to 12, its sugar composition is a small proportion of low-molecular sugars and a large proportion of high-molecular sugars. Therefore, maltodextrin is not easily affected by moisture and is difficult to brown. When the DE value is too high, it will affect the coating effect of maltodextrin on the active material during grinding. Therefore, maltodextrin with a DE value of 10 is selected. Maltodextrin can play a coating role on the active material in the slurry after fine grinding, so that the embedding agent can be evenly distributed on the surface of the spray material during the spraying process, and the embedding agent and the carbon source can cooperate to make the carbon material on the surface of the positive electrode material obtained by sintering have a suitable degree of graphitization.
[0084] In some embodiments, the inlet air temperature of the spray drying is 210°C to 250°C, and the outlet air temperature is 95°C to 110°C. The inlet air temperature can be 210°C, 220°C, 230°C, 240°C, 250°C, or any value therebetween, without limitation. The outlet air temperature can be 95°C, 100°C, 105°C, 110°C, or any value therebetween, without limitation.
[0085] In some embodiments, the frequency of the induced draft fan of the spray drying is 35 Hz to 42 Hz, and specifically can be 35 Hz, 37 Hz, 38 Hz, 39 Hz, 40 Hz, 42 Hz or any value therebetween, which is not limited here.
[0086] In some embodiments, during the spray drying process, the pressure of the compressed air is 0.4 MPa to 1 MPa, specifically 0.4 MPa, 0.6 MPa, 0.8 MPa, 0.9 MPa, 1 MPa or any value therebetween, which is not limited here.
[0087] In some embodiments, the spray drying time is 4 h to 8 h, specifically 4 h, 5 h, 6 h, 7 h, 8 h or any value therebetween, which is not limited here.
[0088] In the present application, the process parameters such as the inlet temperature, time, and compressed air pressure of the spray drying are controlled, and the small particles agglomerate to form secondary particles during the spray drying process, and the encapsulating agent and the carbon source can be evenly distributed on the surface of the secondary particles; and under the action of the dispersant, the carbon source can be more evenly dispersed in the solution, and agglomeration is not likely to occur during spray drying, which is conducive to the formation of a precursor with high sphericity.
[0089] S30, sintering the precursor to obtain a positive electrode material, wherein the sintering process includes a first stage, a second stage and a third stage performed in sequence, wherein the sintering temperature of the first stage is 200°C~600°C, the sintering temperature of the second stage is 650°C~700°C, and the sintering temperature of the third stage is 750°C~800°C.
[0090] In some embodiments, the sintering process is performed in an oxygen-containing atmosphere, and the oxygen concentration in the oxygen-containing atmosphere is ≥ 95%.
[0091] In some embodiments, the sintering process includes a first stage, a second stage and a third stage performed sequentially, the sintering temperature of the first stage is 500°C~600°C, the sintering temperature of the second stage is 650°C~700°C, and the sintering temperature of the third stage is 750°C~800°C.
[0092] In some embodiments, the temperature of the first stage is 200°C to 600°C, specifically 200°C, 300°C, 400°C, 500°C, 570°C, 580°C, 600°C or any value therebetween, which is not limited here.
[0093] In some embodiments, the duration of the first stage is 4 h to 6 h, specifically 4 h, 5 h, 5.5 h, 6 h or any value therebetween, which is not limited here.
[0094] In some embodiments, the temperature of the second stage is 650°C to 700°C, and specifically can be 650°C, 670°C, 680°C, 700°C or any value therebetween, which is not limited herein.
[0095] In some embodiments, the duration of the second stage is 4 h to 6 h, specifically 4 h, 5 h, 5.5 h, 6 h or any value therebetween, which is not limited here.
[0096] In some embodiments, the temperature of the third stage is 750°C-800°C, specifically 750°C, 760°C, 780°C, 790°C, 800°C or any value therebetween, which is not limited here.
[0097] In some embodiments, the duration of the third stage is 3 hours to 8 hours, specifically 3 hours, 4 hours, 5 hours, 6 hours, 7 hours, 8 hours or any value therebetween, which is not limited here.
[0098] In some embodiments, the heating rate of the sintering treatment is controlled at 3°C / min~5°C / min, so that the carbon source material can be fully converted into inorganic carbon and partially achieve graphitization. Controlling the heating rate can also prevent the particles from increasing and causing too little, thereby ensuring the capacity and conductivity of the positive electrode material.
[0099] During the sintering process, the carbon source on the surface of the secondary particles melts first. When the temperature rises to above 200°C, the carbon source dehydrates to form coke-like compounds. After the sintering temperature is further increased, further dehydrogenation and deoxidation are carried out to produce disordered hexagonal carbon planes, that is, graphite microcrystals. At this time, most of the carbon source is converted into disordered carbon, that is, sp3 carbon (amorphous carbon) with disordered structure. The sintering temperature continues to rise, and some graphite microcrystal sheets that are roughly in the same plane gradually combine into a new plane body, that is, short-range ordered sp2 carbon (graphitized carbon). In this application, by controlling the sintering temperature and time, it is beneficial for more sp3 carbon to transform into sp2 carbon. At the same time, segmented high-temperature sintering is used to prevent the matrix material from growing excessively, causing overburning and loss of the capacity of the positive electrode material. And due to the difference in the size of the secondary particles, carbon layers with different sp3 carbon / sp2 carbon ratios are formed on the surfaces of secondary particles of different particle sizes.
[0100] In a third aspect, the present application provides a battery, the battery comprising the positive electrode material of the first aspect or the positive electrode material prepared according to the preparation method of the positive electrode material.
[0101] The battery provided in the present application may be a secondary battery (such as a lithium-ion battery, a sodium-ion battery, etc.), including a housing, an electrode assembly, and an electrolyte. The electrode assembly and the electrolyte are both located in the housing. The housing may be a packaging bag obtained by packaging with a packaging film (such as an aluminum-plastic film), such as a soft-pack battery.
[0102] In other embodiments, the secondary battery may also be a steel shell battery, an aluminum shell battery, etc.
[0103] Figure 1 A schematic diagram of the discharge state of a battery provided in an embodiment of the present application, such as Figure 1 As shown, the battery includes a shell and an electrode assembly, the electrode assembly includes a positive electrode sheet 1, a negative electrode sheet 2 and a separator 3, and the separator 3 is arranged between the positive electrode sheet 1 and the negative electrode sheet 2. The electrode assembly can be a laminated structure, which is formed by alternately stacking the positive electrode sheet 1, the separator 3 and the negative electrode sheet 2 in sequence.
[0104] In other embodiments, the electrode assembly may also be a winding structure, which is formed by stacking a positive electrode sheet, a separator, and a negative electrode sheet in sequence and then winding them.
[0105] In some embodiments, the positive electrode sheet 1 includes a positive electrode current collector 101 and a positive electrode active material layer 102 disposed on at least one surface of the positive electrode current collector 101 .
[0106] In some embodiments, the positive electrode current collector 101 may be aluminum foil or nickel foil, or any composite current collector disclosed in the prior art, such as but not limited to the current collector formed by combining the aforementioned conductive foil (aluminum foil or nickel foil, etc.) and a polymer substrate. The positive electrode active material layer 102 comprises a positive electrode active material, a conductive agent, and a binder, wherein the positive electrode active material is the positive electrode material of the first aspect described above or a positive electrode material prepared according to the preparation method of the positive electrode material described above.
[0107] In some embodiments, the negative electrode sheet 2 includes a negative electrode current collector 201 and a negative electrode active material layer 202 disposed on at least one surface of the negative electrode current collector.
[0108] In some embodiments, the negative electrode current collector 201 can be made of at least one of copper foil, nickel foil, stainless steel foil, titanium foil or a carbon-based current collector, or can be any composite current collector disclosed in the prior art, such as but not limited to a current collector formed by combining the aforementioned conductive foil and a polymer substrate.
[0109] In some embodiments, the negative electrode active material layer 202 includes a negative electrode material, and the negative electrode material includes but is not limited to artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, lithium titanate, etc. The silicon-based material can be selected from at least one of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The tin-based material can be selected from at least one of elemental tin, tin oxide compounds, and tin alloys. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for batteries can also be used. These negative electrode active materials can be used alone or in combination of two or more.
[0110] The battery provided in the embodiment of the present application has the advantages of high capacity, high initial efficiency, long cycle life, excellent rate performance and low expansion. The battery can be a lithium ion battery, a sodium ion battery, a solid electrolyte battery, etc., which is not limited here.
[0111] The following is a further description of the embodiments of the present invention in multiple embodiments. The embodiments of the present invention are not limited to the following specific embodiments.
[0112] Test method: (1) Raman testing of cathode materials At 140 μm Randomly select 3-5 particles within the range of 100 μm, whose particle size is ≤3μm, and then select 3-5 particles whose particle size is ≥8μm; perform Raman point scanning at the center of the particle, and the test conditions are excitation wavelength 532 nm, exposure time 60 s, microscope objective 50X Lwd, detection range 800 ~ 2000 cm-1, and obtain Raman test results. The degree of graphitization is obtained by the area ratio of the peaks at 1340.5 cm-1 and 1599.7 cm-1. D / I G The value of .
[0113] The crystallite size of the graphite crystals on the particle surface of the positive electrode material along the a-axis direction is calculated to be La according to the Tuinstra-Koenig equation. , λ is the excitation wavelength of light in Raman testing.
[0114] (2) Mastersizers 3000 were used to characterize the particle size distribution and volume distribution of the positive electrode material. The specific method is as follows: The particle size test method refers to GB / T 19077-2016. The volume-based cumulative particle size distribution can be conveniently determined using a laser particle size analyzer, such as the Mastersizer 3000 laser particle size analyzer from Malvern Instruments Ltd., UK.
[0115] D10 represents the particle size corresponding to 10% of the cumulative particle size distribution percentage of the powder, D50 represents the particle size corresponding to 50% of the cumulative particle size distribution percentage, and D90 represents the particle size corresponding to 90% of the cumulative particle size distribution percentage.
[0116] Particle size distribution width for:
[0117] D90, D10, and D50 are the particle size ratio parameters in the range of 1.5μm~11μm respectively.
[0118] (3) Testing method for specific surface area of positive electrode materials: The specific surface area of the positive electrode material was tested using the Tristar3020 specific surface area and pore size analyzer from the American company McMeretic. A certain mass of powder was weighed and completely degassed under vacuum heating to remove the surface adsorbent. The specific surface area of the particles was calculated by the amount of nitrogen adsorbed using the nitrogen adsorption method. The unit is m 2 / g.
[0119] (4) Positive electrode material tap density test: The tap density tester (model: DAT-4-220) produced by Contacam Instrument Trading (Shanghai) Co., Ltd. of the United States was used. The steps are as follows: 1. Clean the measuring cylinder and weigh the mass of the measuring cylinder as m1; 2. Add about 50g of sample into the measuring cylinder, try to make the sample surface level, and wipe the surrounding area with a paper towel; 3. Weigh the total mass of the sample and the measuring cylinder as m2; 4. Place the measuring cylinder on the vibration table and fix it with three symmetrical fixing feet; 5. Turn on the instrument and set the vibration times to 5000 times; turn on the vibration switch, and the instrument will automatically stop after vibrating the specified number of times; 6. Take out the measuring cylinder and read the volume of the sample. If the sample surface is horizontal after tapping, read the volume directly; if it is a diagonal line, take the average value V of the readings at the highest and lowest points; tap density = (m2-m1) / V, unit is g / cm 3 .
[0120] (5) Compacted density test of positive electrode materials: The compaction density of the positive electrode material was tested using a compaction density tester model 4350 from Carver, USA. The steps are as follows: 1g of sample was weighed and placed in a mold with a pressure of 3T for 30s. After compaction, the height was measured and the compaction density was calculated in g / cm 3 .
[0121] (6) IPC test method for positive electrode materials: Take 0.3g of the sample to be tested and dissolve it in aqua regia, cool and dilute to a volume of 100ml to prepare the mother solution for determination; take 1mL of the mother solution for determination, dilute it 100 times, and test the content of the main elements Li, Ni, Co, and Mn and the content of other elements such as doping elements by ICP. The determination is carried out using Agilent 5110 ICP-OES detection equipment.
[0122] (7) Test method for oil absorption value of positive electrode material: The oil absorption value is tested using an ASAHI S-500 oil absorption value tester produced by Japan's ASAHI Metal Industries Co., Ltd. The oil absorption value is the amount of linseed oil added when the torque generated by the change in viscosity characteristics reaches 70% of the maximum torque, and the unit is mL / 100g.
[0123] (8) Powder resistivity test method of positive electrode material: The powder resistivity of the positive electrode material was measured using a resistivity tester (Suzhou Jingge Electronics ST-2255A).
[0124] (9) Mass content of carbon in positive electrode material: The combustion-infrared absorption method is used to burn the sample in a high-temperature oxygen flow, and the carbon is converted into carbon dioxide ( ), detected by infrared absorption spectroscopy The specific operation includes: grinding the solid cathode material sample into a uniform powder, placing it in a high temperature furnace (2000℃), and introducing oxygen to assist combustion. :The gas after combustion passes through the impurity removal device (such as dust removal pipe, desulfurization agent) to remove interfering substances (such as , ). The gas enters the infrared detection cell and infrared light of a specific wavelength is Absorption. Calculated from absorbance according to the Lambert-Beer law The concentration is then converted into the mass content of carbon element.
[0125] (10) pH value test of positive electrode material: Take about 5g of positive electrode material sample, add 45mL of water, ultrasonicate for 5min, take it out and let it stand for 10min. After the pH meter is calibrated, insert the composite electrode into the upper clear liquid to be measured. Calculate the pH value of the solution based on the potential difference between the measuring electrode and the reference electrode.
[0126] (11) Test on the mass content of magnetic substances in positive electrode materials: Weigh 200±5 g of sample into a 500ml plastic bottle, add a clean magnetic bar and 300ml of anhydrous ethanol to the bottle, cover the bottle cap, and align it on the aligner for 30 minutes. Use the magnetic bar to absorb magnetic metal elements such as iron, nickel, chromium, and zinc in the material. Open the bottle cap, align the clean conical bottle with the mouth of the bottle, use another magnetic bar to transfer the magnetic bar in the bottle to the conical bottle outside the bottle, clean the non-magnetic material remaining on the magnetic bar in the conical bottle, add 6mL of hydrochloric acid and 2mL of nitric acid, heat on a hot plate for about 30 minutes, filter and fix the volume, and use an inductively coupled plasma optical emission spectrometer (ICP-OES) to detect the content of magnetic substances.
[0127] (12) Sphericity test: According to the properties of the sample, the wet circulation module LIXELL is selected for dispersion, and the sample is dispersed into individual particles to ensure that the particles do not block or overlap each other in the test area, so as to obtain a clear particle image. The stroboscopic light emitted from the stroboscopic light source is converted into parallel light through the beam expander, and the dispersed individual particles are irradiated in the test area. Through a proprietary optical imaging system, the image of the particle is projected onto the high-speed imaging system CMOS, and photographed at a rate of up to 500 frames per second to obtain a clear image of each particle. The collected particle images are processed and analyzed using analysis software. The software automatically calculates the sphericity of each particle according to a preset algorithm. Sphericity is determined by comparing the actual surface area of the particle with the surface area of a perfect sphere of the same volume, and the calculation formula is: Sphericity = (square of the perimeter) / (4π×area). The closer the sphericity value is to 1, the closer the particle is to a perfect sphere.
[0128] (13) Electrochemical performance test: The positive electrode material was mixed with conductive carbon black and binder PVDF (polyvinylidene fluoride) in a mass ratio of 80:10:10, and NMP (N-methylpyrrolidone) was added to make a uniform slurry. The slurry was evenly coated on aluminum foil and placed in a 100°C oven for drying for 12 hours. After drying, it was rolled at a pressure of 10 MPa and cut into circular pole pieces with a diameter of 14 mm. The negative electrode used a Li metal sheet with a diameter of 14 mm. The lithium-ion battery was assembled according to the CR2025 button battery in industry. The diaphragm was Cellgard diaphragm, and the electrolyte used an equal amount of ethylene carbonate (EC), polycarbonate (PC) and diethyl carbonate (DEC) with 1 mol / L LiPF6 as the electrolyte. The positive pole piece, diaphragm, negative pole piece and electrolyte were assembled into a button battery in an Ar gas glove box with a water content and an oxygen content of less than 0.5 ppm.
[0129] Capacity test system: The blue electric test system is used for electrical performance testing (charge and discharge voltage is 2.0~3.75V, temperature condition is 25℃), the current size of the first three cycles is 0.1C, and then the current is increased to 1C, and the first cycle capacity, discharge specific capacity and first coulombic efficiency are measured.
[0130] The test results are shown in Table 2.
[0131] Example 1 (1) Add 10 kg of pure water to a ball mill, add 3 wt% of the total mass of the iron source and the manganese source, fructose and maltose as carbon sources, wherein the mass ratio of fructose to maltose is 5:5, and then add 1 wt% of the total mass of the iron source and the manganese source, polyethylene glycol PEG, as a dispersant, and stir for 20 minutes to obtain a first mixture. Add manganese tetraoxide, iron phosphate, and titanium dioxide in a molar ratio of n(Mn):n(Fe):n(Ti)=0.6:0.39:0.01 to the first mixture, and then add phosphoric acid to supplement the lack of phosphorus source and an excess of 2 wt% of lithium carbonate as a lithium source, and continue high-speed ball milling to control the D50 of the finely ground liquid to be 0.3μm±0.02μm.
[0132] (2) After fine grinding, 1 wt.% of maltodextrin with a DE value of 10 was added to the total mass of the iron source and the manganese source as 100 wt%, and the mixture was stirred for 10 minutes to obtain a spray slurry. The slurry was pumped into the spray dryer by a peristaltic pump, the inlet air temperature was controlled at 230 °C, the outlet air temperature was controlled at 100 °C, the induced draft fan frequency was 42 Hz, the compressed air was 0.3 MPa, and the atomizer frequency was 350 Hz. A spherical precursor with a D50 of 8 ± 2 μm was prepared by spray drying in a two-fluid spray dryer.
[0133] (3) The spherical precursor was sintered in a nitrogen atmosphere with a heating rate controlled at 3 °C / min. The precursor was kept at 400 °C, 700 °C, and 750 °C for 6 h, 5 h, and 5 h, respectively, and then cooled to obtain the positive electrode material.
[0134] The positive electrode material prepared in Example 1 of the present application includes lithium iron manganese phosphate and a carbon layer located on the surface of the lithium iron manganese phosphate. The chemical formula of the positive electrode material is LiMn 0.6 Fe 0.39 Mg 0.01 PO4·C.
[0135] Figure 2 This is a SEM image of the positive electrode material prepared in Example 1 of the present application, as shown Figure 2 As shown, the positive electrode material particles are spherical particles. Figure 3 The Raman spectrum of the positive electrode material prepared in Example 1 of the present application is as follows: Figure 3 As shown, 30 particles were selected for Raman testing. Figure 4 This is a schematic diagram of 30 test points selected for the Raman test of the positive electrode material prepared in Example 1 of the present application, and the particle size of the corresponding particles is obtained from the diagram.
[0136] Example 2 The difference from Example 1 is: (2) After fine grinding, 0.5 wt.% of maltodextrin with a DE value of 10 was added based on the total mass of the iron source and the manganese source as 100 wt%, and the mixture was stirred for another 10 minutes to obtain a spray slurry.
[0137] Example 3 The difference from Example 1 is: (2) After fine grinding, 1.5 wt.% of maltodextrin with a DE value of 10 was added based on the total mass of the iron source and the manganese source as 100 wt%, and the mixture was stirred for another 10 minutes to obtain a spray slurry.
[0138] Example 4 The difference from Example 1 is: (3) The lithium manganese iron phosphate precursor is sintered in a nitrogen atmosphere, the heating rate is controlled at 3 °C / min, and the materials are kept at 400 °C, 700 °C, and 750 °C for 6 hours, 5 hours, and 3 hours, respectively. The organic carbon in the material is fully converted into inorganic carbon and graphitized by the gradient temperature setting, and then cooled to obtain the positive electrode material.
[0139] Example 5 The difference from Example 1 is: (3) The lithium manganese iron phosphate precursor is sintered in a nitrogen atmosphere, the heating rate is controlled at 3 °C / min, and the materials are kept at 400 °C, 700 °C, and 750 °C for 6 hours, 5 hours, and 7 hours, respectively. The organic carbon in the material is fully converted into inorganic carbon and graphitized by the gradient temperature setting, and then cooled to obtain the positive electrode material.
[0140] Example 6 The difference from Example 1 is: (3) The lithium manganese iron phosphate precursor is sintered in a nitrogen atmosphere, the heating rate is controlled at 3 °C / min, and the materials are kept at 400 °C, 700 °C, and 770 °C for 6 hours, 5 hours, and 5 hours, respectively. The organic carbon in the material is fully converted into inorganic carbon and graphitized by the gradient temperature setting, and then cooled to obtain the positive electrode material.
[0141] Example 7 The difference from Example 1 is: (3) The lithium manganese iron phosphate precursor is sintered in a nitrogen atmosphere, the heating rate is controlled at 3 °C / min, and the materials are kept at 400 °C, 700 °C, and 730 °C for 6 hours, 5 hours, and 5 hours, respectively. The organic carbon in the material is fully converted into inorganic carbon and graphitized by the gradient temperature setting, and then cooled to obtain the positive electrode material.
[0142] Example 8 The difference from Example 1 is that: (1) 10 kg of pure water is added to the ball mill, 4 wt% of the total mass of the iron source is added as a carbon source, and the mass ratio of fructose to maltose is 5:5, and 1 wt% of the total mass of the iron source is added as a dispersant, and the first mixture is obtained after ball milling and stirring for 20 minutes. Manganese tetraoxide, iron phosphate, and titanium dioxide are added to the first mixture in a proportion of n(Mn):n(Fe):n(Ti)=0.6:0.39:0.01, and phosphoric acid is added to supplement the lack of phosphorus source and an excess of 2 wt% of lithium carbonate as a lithium source, and high-speed ball milling is continued to control the D50 of the finely ground liquid to be 0.3μm±0.02μm.
[0143] Example 9 The difference from Example 1 is: (2) After fine grinding, 1 wt.% of maltodextrin with a DE value of 10 was added to the total mass of the iron source and the manganese source as 100 wt%, and the mixture was stirred for another 10 minutes to obtain a spray slurry. The slurry was pumped into the spray dryer by a peristaltic pump, the inlet air temperature was controlled at 230 °C, the outlet air temperature was controlled at 100 °C, the induced draft fan frequency was 42 Hz, the compressed air was 0.7 MPa, and the atomizer frequency was 350 Hz. A spherical precursor with a D50 of 8 ± 2 μm was prepared by spray drying in a two-fluid spray dryer.
[0144] Example 10 The difference from Example 1 is: (1) Add 10 kg of pure water to a ball mill, add 4 wt% of the total mass of the iron source, fructose and maltose as carbon sources, where the mass ratio of fructose to maltose is 5:5, and then add 1 wt% of the total mass of the iron source, polyethylene glycol PEG, as a dispersant, and stir for 20 minutes to obtain a first mixture. Add iron phosphate and titanium dioxide in a molar ratio of n(Fe):n(Ti)=0.99:0.01 to the first mixture, then add phosphoric acid to supplement the lack of phosphorus source and an excess of 2 wt% of lithium carbonate as a lithium source, continue high-speed ball milling, and control the D50 of the finely ground liquid to be 0.3μm±0.02μm.
[0145] (3) The spherical precursor was sintered in a nitrogen atmosphere with a heating rate controlled at 3 °C / min. The precursors were kept at 400 °C, 720 °C, and 770 °C for 6 h, 5 h, and 5 h, respectively, and then cooled to obtain the positive electrode material.
[0146] Comparative Example 1 The difference from Example 1 is: (1) Add an iron source and a manganese source to a ball mill, with the total mass of the iron source and the manganese source being 100 wt%, add an equal mass of pure water, and then add 3 wt % of fructose and maltose as carbon sources, wherein the mass ratio of fructose to maltose is 5:5. Stir for 10 minutes to evenly distribute the carbon source in the slurry, thereby obtaining a first mixture.
[0147] Comparative Example 2 The difference from Example 1 is: (2) The finely ground spray slurry was pumped into the spray dryer by a peristaltic pump, the inlet air temperature was controlled at 230°C, the outlet air temperature was controlled at 100°C, the induced draft fan frequency was 42 Hz, the compressed air was 0.3 MPa, and the atomizer frequency was 350 Hz. The spherical lithium manganese iron phosphate precursor with a D50 of 8±2 μm was prepared by spray drying in a two-fluid spray dryer.
[0148] Comparative Example 3 The difference from Example 1 is: (3) The lithium manganese iron phosphate precursor was sintered in a nitrogen atmosphere, the heating rate was controlled at 3 °C / min, and the temperature was kept at 680 °C for 10 hours, and then cooled to obtain the positive electrode material.
[0149] Table 1 Comparison of positive electrode materials of the embodiment and the comparative example
[0150] The button cell containing the positive electrode material was subjected to electrochemical testing, and the test results are shown in Table 2 below.
[0151] Table 2 Comparison of the physical and chemical properties of the positive electrode materials of the embodiments and the comparative examples and the performance of the batteries prepared therefrom
[0152] According to the test data of Examples 1 to 10 (S1 to S10), the present application controls the graphite crystallite size on the surface of the first particle and the second particle to satisfy: 1.3≤La2 / La1≤1.91, so that the surface of the second particle with a large particle size forms a graphite crystallite with a larger size along the a-axis direction. The large-sized graphite crystallite along the a-axis direction can transmit electrons faster. Due to the ion-coupled electron transfer, the transmission efficiency of lithium ions on the surface of the second particle can be greatly improved, which is beneficial to improve the lithium ion insertion and extraction efficiency. The surface of the first particle with a small particle size forms a graphite crystallite with a smaller size along the a-axis direction. Since the first particle itself has a smaller particle size, the first particle can have a higher ion and electron transmission efficiency. The graphite crystallite with a smaller size along the a-axis direction has less effect on the electron and ion transmission of the first particle, so that the first particle and the second particle in the positive electrode material can present a high degree of lithium ion conduction consistency as a whole. In addition, the formation of a smaller graphite crystallite size on the surface of the first particle can inhibit the growth of primary particles in the first particle and reduce the capacity attenuation caused by excessive growth of primary particles in the first particle. The positive electrode material of the present application has good conductivity, capacity and rate performance.
[0153] According to the test data of Example 9 and Example 1, it can be seen that the compressed air pressure is too high during the spray drying process, resulting in excessive fluctuations in the particle size of the spherical precursor, and the span value of the positive electrode material finally obtained is too large, the tap density of the positive electrode material decreases, and the compaction density also decreases slightly; due to the increase in the proportion of small-size particles, the specific surface area of the positive electrode material also increases, the side reactions intensify, and the capacity is slightly reduced compared to Example 1.
[0154] According to the test data of Comparative Example 1 (D1) and Example 1, no dispersant was added to Comparative Example 1, and the materials were fully mixed only by mechanical stirring. Figure 5 This is the EDS spectrum of carbon elements on the surface of the positive electrode material prepared in Comparative Example 1 of the present application, such as Figure 5 As shown, there is obvious carbon enrichment on the surface of the positive electrode material, and the uniformity of carbon material coating is reduced. Due to the aggregation of carbon materials, the accuracy of Raman test is reduced, so Raman test is not performed. The proportion of amorphous carbon (sp3 carbon) on the surface of positive electrode material particles is higher, which is easy to form a poor conductive area, the powder resistivity of the positive electrode material increases, and the capacity and initial efficiency of the positive electrode material are reduced.
[0155] According to the test data of Comparative Example 2 (D2) and Example 1, if no carbon source is added after grinding, the retained carbon source on the surfaces of both large and small particles will be reduced. In the subsequent sintering process, the carbon source on the surface of the particles is transformed from amorphous carbon to graphitized carbon as much as possible, but the size of the graphite crystallites is difficult to increase significantly, especially the size of the graphite crystallites on the surface of the large-sized second particles decreases, and the La2 / La1 ratio is too small, resulting in a decrease in the electronic conductivity of the large-sized second particles and a decrease in the electronic conductivity of the positive electrode material.
[0156] According to the test data of Comparative Example 3 (D3) and Example 1, the sintering process does not adopt step-by-step temperature increase, the sintering temperature is not gradually increased, the conversion of amorphous carbon on the particle surface to graphitized carbon is reduced, the graphite crystallite size on the surface of the second particles with large particle size is too large, the difference between the graphite crystallite size on the surface of the second particles with large particle size and the graphite crystallite size on the surface of the second particles with small particle size is too large, and the La2 / La1 ratio is too large, resulting in an increase in the difference in lithium ion insertion and extraction performance between particles of different particle sizes in the positive electrode material, a decrease in the electronic conductivity of the positive electrode material, and a decrease in the capacity of the positive electrode material.
[0157] The above description is only the preferred embodiment of the present application and is not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.
Claims
1. A positive electrode material, characterized in that: The positive electrode material comprises a core and a carbon material located on at least a portion of the surface of the core; the positive electrode material comprises first particles with a particle size of ≤3 μm and second particles with a particle size of ≥8 μm; The positive electrode material is tested by Raman, and the crystallite size of the graphite crystal on the particle surface of the positive electrode material along the a-axis direction is calculated according to the Tuinstra-Koenig equation as La, , λ is the excitation wavelength of light in Raman testing; The graphite crystallite size on the surface of the first particle is La1 nm, the graphite crystallite size on the surface of the second particle is La2 nm, and the positive electrode material satisfies: 1.3≤La2 / La1≤1.
91.
2. The positive electrode material according to claim 1, characterized in that The I D / I G The ratio is A, the I D / I G The ratio is B, 1.25≤A / B≤1.
7.
3. The positive electrode material according to claim 2, characterized in that The positive electrode material satisfies at least one of the following characteristics: (1)2.6≤A≤3.2; (2)1.8≤B≤2.4; (3) 5.0≤La1≤6.8; (4)7.5≤La2≤10.
2.
4. The positive electrode material according to claim 1, characterized in that The particle size number distribution curve of the positive electrode material has a peak that conforms to the Voigt function distribution, and the particle size distribution width of particles in the range of 1.5 μm to 11 μm is Span (b), which satisfies 1.7<Span (b)<2.
4.
5. The positive electrode material according to any one of claims 1 to 4, characterized in that The chemical general formula of the positive electrode material is Li n Mn x Fe y M 1-x-y PO4, where 0.9 ≤ n ≤ 1.2, 0 ≤ x < 0.8, 0.2 < y < 1, and M includes at least one of Ti, Nb, Ta, Ba, Sr, Mg, Zn, V, Mo, Y, and W.
6. The positive electrode material according to any one of claims 1 to 4, characterized in that The positive electrode material includes secondary particles formed by agglomeration of primary particles; the positive electrode material satisfies at least one of the following characteristics: (1) The particle size of the primary particles is 50 nm to 250 nm; (2) The sphericity of the secondary particles is 0.85-0.
90.
7. The positive electrode material according to any one of claims 1 to 4, characterized in that The positive electrode material satisfies at least one of the following characteristics: (1) The tap density of the positive electrode material is 1.4 g / cm 3 ~1.85 g / cm 3 ; (2) The specific surface area of the positive electrode material is 7 m 2 / g~15 m 2 / g; (3) The compaction density of the positive electrode material is 2.05 g / cm 3 ~2.35 g / cm 3 ; (4) The pH value of the positive electrode material is 9.5-10.
5.
8. The positive electrode material according to any one of claims 1 to 4, characterized in that The positive electrode material satisfies at least one of the following characteristics: (1) The oil absorption value of the positive electrode material is 20 mL / 100g~40 mL / 100g; (2) The powder resistivity of the positive electrode material is 10-100 Ω·m.
9. The positive electrode material according to any one of claims 1 to 4, characterized in that The positive electrode material satisfies at least one of the following characteristics: (1) The mass content of carbon element in the positive electrode material is 1.4wt%~1.7wt%; (2) The mass content of the magnetic substance in the positive electrode material is 0.1~0.75 mg / kg.
10. A battery, characterized in that: The battery comprises the positive electrode material according to any one of claims 1 to 9.
Citation Information
Patent Citations
Positive pole piece, secondary battery, battery module, battery pack and electric device
CN117083729A
Negative pole piece, battery, battery pack and electric equipment
CN117117091A
Positive pole piece, battery and electric equipment
CN119340393A
Electrode material for lithium ion secondary batteries, and lithium ion secondary battery arranged by use thereof
JP2015079681A
Active materials for lithium ion batteries
US20140377659A1
Cited By
Low-polarization single-crystal ternary positive electrode material prepared by independent fusion and application thereof
CN120709357A